2008
DOI: 10.1007/s11307-008-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-free Viral Capsids as Carriers for Positron Emission Tomography Radiolabels

Abstract: These studies provide further insight into the pharmacokinetic behavior of nanomaterials and serve as a platform for the future development of targeted imaging and therapeutic agents based on mtMS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…MS2 particles have been labeled with [ 18 F]-fluorobenzaldehyde and evaluated in rats. These experiments showed that although [ 18 F]fluorobenzaldehyde is rapidly cleared from the circulation, [ 18 F]-MS2 particles can persist for at least 3 hours (Figure 3) [76**]. In a different study, iron oxide nanoparticles and 18 F-fluoride were encapsulated into envelopes derived from Hemagglutinating virus of Japan (HVJ), and achieved a similarly high signal-to-noise imaging resolution in PET.…”
Section: From Engineering To Potential Applications In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…MS2 particles have been labeled with [ 18 F]-fluorobenzaldehyde and evaluated in rats. These experiments showed that although [ 18 F]fluorobenzaldehyde is rapidly cleared from the circulation, [ 18 F]-MS2 particles can persist for at least 3 hours (Figure 3) [76**]. In a different study, iron oxide nanoparticles and 18 F-fluoride were encapsulated into envelopes derived from Hemagglutinating virus of Japan (HVJ), and achieved a similarly high signal-to-noise imaging resolution in PET.…”
Section: From Engineering To Potential Applications In Medicinementioning
confidence: 99%
“…In contrast, [ 18 F]-MS2 remained in circulation for the duration of the experiment (3 hours) as seen in the figure. Reproduced with permission from reference [76]. …”
Section: Figurementioning
confidence: 99%
“…A popular click chemistry strategy used with VNPs is copper-catalyzed azide-alkyne cycloaddition (CuAAC) between azides and alkynes in the presence of Cu(I), irreversibly yielding the biocompatible 1,4-substituted triazole derivative (19, 28, 3337). In addition, azo-coupling can be used to introduce payloads into VNPs (32, 3840). Typically, an aldehyde is first introduced onto the VNP surface by azo-coupling to a bifunctional linker.…”
Section: Modification Strategies: From Scaffolds To Functional Entitiesmentioning
confidence: 99%
“…The first studies on the generation of nanoparticles for magnetic resonance imaging applications and the first comparisons of interior versus exterior cargo strategies appeared in the mid 2000s [271,272]. Following these reports, MS2 VLPs were loaded with positron emission tomography radiolabels [273]. To date, MS2 phages and VLPs have played a leading role in bioimaging studies.…”
Section: Nonvaccine Applicationsmentioning
confidence: 99%